ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL TERHADAP PROSEDUR PEMBERIAN KREDIT KEPADA USAHA MIKRO PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk - B51108117, Dedi Suriyadi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This study aims to determine how the system of internal control over micro-enterprise lending procedures at PT. Bank Rakyat Indonesia (Persero) Tbk and what factors are causing a credit crunch or credit macet.Penelitian uses a qualitative approach that uses descriptive method with case studies on systems and procedures for granting credit at PT. Bank Rakyat Indonesia (Persero) Tbk. The data analysis technique used in this study is the use of data analysis techniques organizational structure chart, system flowchart (Flowchart), internal control analysis technique using questionaire (ICQ), technical analysis of questionnaires and analysis techniques using test compliance (compliance test). The sample selection of this study using proposive sampling with the aim that can be obtained samples terwakili.Berdasarkan research by the author, the author can draw the conclusion that the system of internal control at PT. Bank Rakyat Indonesia (Persero) Tbk has gone well, just need to be improved in order to better.